ARGONAUTE 2 increases rice susceptibility to rice black-streaked dwarf virus infection by epigenetically regulating HEXOKINASE 1 expression - Wang, Zhaoyun; Chen, Dongyue; Sun, Feng; Guo, Wei; Wang, Wei; Li, Xuejuan; Lan, Ying; Du, Linlin; Li, Shuo; Fan, Yongjian; Zhou, Yijun; Zhao, Hongwei; et al. (Wiley, 2021)
ARGONAUTE (AGO) proteins play crucial roles in plant defence against virus invasion. To date, the role of OsAGO2 in rice antiviral defence remains largely unknown. In this study, we determined that the expression of OsAGO2 in rice was induced upon rice black‐streaked dwarf virus (RBSDV) infection. Using transgenic rice plants overexpressing OsAGO2 and Osago2 mutants generated through transposon‐insertion or CRISPR/Cas9 technology, we found that overexpression of OsAGO2 enhanced rice susceptibility to RBSDV infection. Osago2 mutant lines exhibited strong resistance to RBSDV infection through the elicitation of an early defence response, including reprogramming defence gene expression and production of reactive oxygen species (ROS). Compared to Nipponbare control, the expression level of OsHXK1 (HEXOKINASE 1) increased significantly, and the methylation levels of its promoter decreased in the Osago2 mutant on RBSDV infection. The expression profile of OsHXK1 was the opposite to that of OsAGO2 during RBSDV infection. Overexpression of OsHXK1 in rice also induced ROS production and enhanced rice resistance to RBSDV infection. These results indicate that OsHXK1 controls ROS accumulation and is regulated by OsAGO2 through epigenetic regulation. It is noteworthy that the Osago2 mutant plants are also resistant to southern rice black‐streaked dwarf virus infection, another member of the genus Fijivirus. Based on the results presented in this paper, we conclude that OsAGO2 modulates rice susceptibility to fijivirus infection by suppressing OsHXK1 expression, leading to the onset of ROS‐mediated resistance. This discovery may benefit future rice breeding programmes for virus resistance.